Damping Impact on 1-Dimensional Ultrasonic Vibration Assisted Turning (UVAT) Machining - Arafat, Mohammad; Ibrahim, Rasidi; Hambali, Muhammad Agung (Journal of Advanced Mechanical Engineering Applications, 2020)
Ultrasonic vibration assisted machining has already achieved a great attraction due to its efficiency in machining. In this type of machining process, vibration is one of the critical factor because of the cutting tool principle itself. It is known that vibration in machining disrupts surroundings by creating noise as well as cutting tool life, machining accuracy, and workpiece surface quality also affected by it. As a result, the effect of resonance is commonly a large amount of vibration that should be avoided. Furthermore, the low static stiffness and material damping characteristics of workpiece materials also causes a high dynamic compliance. This can lead to instability of the chip removal process. One the other hand, frequency (â‰¥20kHz) of electrical energy is converted into vibration energy by piezoelectric actuators, which tends to transmit vibration on the edge of the cutting tool and tool post. The function of actuators enables cutting tool actuates on the workpiece, which has no continuous interaction between cutting tip and workpiece. In addition, this machining process refer to the maximization of vibration energy usage only in the cutting tool rather than transmitting vibration other parts besides cutting tool. Therefore this paper investigated, a vibration performance in the cutting tool by adding isolator pad as damping element in the static zone of tool holder in order to reduce the resonance that generated during the machining process. At the end, results showed significant changes in amplitude and surface roughness. Then finally this paper provided an experimental analysis of damping impact on one-dimensional ultrasonic assisted turning machining.